Molecular Mechanisms and Drug Development in Aquaporin Water Channel Diseases: The Translocation of Aquaporin-5 From Lipid Rafts to the Apical Plasma Membranes of Parotid Glands of Normal Rats and the Impairment of It in Diabetic or Aged Rats - Yasuko Ishikawa; Noriko Inoue; Yuan Zhenfang; Yoshiko Nakae (Elsevier, 2004)
Salivary secretion from rat salivary glands occurs in response to stimulation by acetylcholine and norepinephrine released from nerve endings. Aquaporin-5 (AQP5) localizes in lipid rafts under control conditions and is induced to traffic to the apical plasma membrane in interlobular ducts of rat parotid glands by the activation of M3 muscarinic acetylcholine receptors or α1-adrenoceptors. This review will focus on the mechanisms of the translocation of AQP5 from lipid rafts to the apical plasma membrane in the interlobular duct cells of parotid glands of normal rats and the impairment of its translocation in diabetic or senescent rats. Keywords:: aquaporin-5, [Ca2+]i, lipid raft, interlobular duct, parotid gland